94 Simulation scenario beta-testing: increasing the fidelity. (17th November 2016) - Sivakumar, C; Taylor, S; Meznikova, K; Ahmed, S; Makwana, S; Kadri, S; Gopal, A
Abstract : Background: Undergraduate medical students from the Hull York Medical School are taught to use simulation 1 to create and run a high fidelity simulated scenario to teach their peer group about managing simple medical emergencies at Hull Institute of Learning and Simulation through a student-selected component. 2 An innovative fast feedback loop was used by students to create, test and improve the scenario over a short time period (akin to software beta-testing). The optimum number of cycles necessary to produce a scenario of strong fidelity and value to the learner was identified. Methodology: The scenario was tested on five occasions, each with a fresh participant. User feedback from post-scenario questionnaire quantitatively and qualitatively assessed educational value and fidelity to identify improvements for the scenario. This yielded a scenario independently assessed on day 5 to be of professional quality and value. Statistical analysis was performed on feedback questionnaires (Mann-Whitney U test), testing for gross global improvement across all numerical domains of the questionnaire (relevance, effectiveness and quality of the pre-brief, scenario and debrief) and comparing them between participants. Outcomes: There was a significant difference between the first(5.3 ± 0.7) and second cycle (8.7 ± 0.5) (p = 0.0002), between cycles 2–3 (9.7 ± 0.5) (p = 0.003) and 3–4 (8.2 ± 1.1) (p = 0.002). However, cycles 4–5 (8.7 ± 0.7) did not show a significant difference in fidelity (p = 0.2). This and qualitative feedback suggests that three cycles are sufficient to achieve a sufficiently high level of fidelity and boost instructor competence. Conclusion: Scenario beta-testing is an excellent method of increasing scenario fidelity and providing high-yield tutor experience, especially if tutors are simulation-naive, and three cycles is suggested as an optimal. References: Gopal A, Purva M. A pilot of a simulation scenario scripting workshop for medical students: exposing students to teaching and learning using simulation-based medical education. BMJ STEL 2014;1 (Suppl 1):A1–A88. Fent G, Gopal A, Purva M. Simulation based medical education as a student selected component for medical students. BMJ STEL 2015;1 (Suppl 2):A1–A67.